Tinjauan Yuridis Perjanjian Pranikah Sebagai Perlindungan Hak Ahli Waris Atas Harta Bersama Yang Menjadi Warisan - Bilqis, Najwa (Jurnal Hukum Positum, 2024)
Heirs have been regulated in the Civil Code or Burgerlijk Wetboek and the Compilation of Islamic Law, but there are still conflicts over inheritance because there is no separation between personal property and joint property that will later become inheritance. The urgency of this research is that the researcher found previous research discussing prenuptial agreements as a form of legal protection for prospective husbands and wives who make them, but the researcher has not found previous research discussing prenuptial agreements as a form of legal protection for heirs who are still minors. This research uses normative legal research methods as a way of studying this research. And from the results of this research it can be concluded that the separation of personal property and joint property in a prenuptial agreement can minimize conflicts related to inheritance and as legal protection for heirs, especially heirs who are still minors.